Analysis on Worker Productivity at SKPD B1 Office Building Construction Project in Pekanbaru - Rodo Hutagalung; Rian Trikomara; Hendra Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Pekanbaru City is one of the developing cities aimed by investors. Pekanbaru City has high economic growth, migration, and urbanization rate. Pekanbaru is the capital city of Riau Province and the central government office is located in this city.The economic and population growth in Pekanbaru City has lead to the more demanding administrative services to support the city development.In construction project schedule, worker productivity should be analyzed to determine the work duration and number of workers. Worker productivity indicates the amount of work that could be done by workers in a specified amount of time, based on the project schedule. Worker productivity is greatly influenced by the social background, age, education, and experience of the worker.This study aims to analyze the productivity of workers at SKPD B1 office building construction project in Pekanbaru.Based on the analysis results, the productivity of workers on column, beam, and slab rebar detailing are similar to the productivity value calculated in the previous study by M Shaleh (2010). This is due to the similarity in the volume of the work. However the result of this study varies significantly relative to the productivity value acquired from the provision: “Peraturan Menteri Pekerjaan Umum”, though the provision doesn’t provide details on the dimension of the column, beam, and slab.Keywords: duration, worker productivity, worker index, construction project, SKPD B1 building